tương tự nhé
a, \(x\left(x^2+1\right)-\left(3x-2x^2\right)3x=x^3+x-9x^2+6x^3=7x^3-9x^2+x\)
b, \(xy^2\left(x-xy\right)-x\left(x+y\right)+xy\left(2x^2-2xy^2\right)\)
\(=x^2y^2-x^2y^3-x^2-xy+2x^3y-2x^2y^3=x^2y^2-3x^2y^3-x^2-xy+2x^3y\)
c, \(-x\left(2x+2\right)\left(x^2-x+1\right)=-2\left(x+1\right)\left(x^2-x+1\right)=-2\left(x^3+1\right)=-2x^3-2\)
d) \(\left(4x-1\right)\left(3x+1\right)-5x\left(x-3\right)-\left(x-4\right)\left(x-3\right)\)
\(=12x^2+4x-3x-1-5x^2+15x-x^2+7x-12\)
\(=11x^2+23x-13\)
e) \(\left(5x-2\right)\left(x+1\right)-3x\left(x^2-x-3\right)-2x\left(x-5\right)\left(x-4\right)\)
\(=5x^2+5x-2x-2-3x^3+3x^2+9x-2x\left(x^2-9x+20\right)\)
\(=-3x^3+8x^2+12x-2-2x^3+18x^2-40x\)
\(=-3x^3+26x^2-28x-2\)